Planar Magnetic Actuation for Soft and Rigid Robots Using a Scalable Electromagnet Array - Li, Xiaosa; Lu, Chengyue; Song, Ziwu; Ding, Wenbo; Zhang, Xiao-Ping (IEEE robotics and automation letters, 2022)
Magnetic actuation system manipulates micro soft or rigid robots by a controllable magnetic field to move them freely in the narrow or enclosed space, which has demonstrated its huge potential in medical interventional surgery and drug delivery. However, the limited working space of paired or area-centered electromagnets restricts its practical applications. In this paper, we propose a convenient coils drive scheme for the scalable electromagnet array, and present an efficient planar magnetic actuation system with a spacious workspace. During the actuation process, our system activates selectively the effective electromagnets neighboring to the magnetic robot by coil selectors, and generates an alternating magnetic field with sufficient gradients to guide the robot's orientation and position. For the soft magnetic pipe, our system can push it to perform the continuous deflections around the stand columns on the plane. For the rigid magnetic cube, the designed magnetic-quadrupole structure allows it to receive various forces from different directions, and achieve a stable displacement in the heterogeneous magnetic field.